The Role of the L1 in EMI classroom practices - Balbina Moncada-Comas (Universitat Autònoma de Barcelona, 2022)
English-medium instruction (EMI) affects lecturers' classroom practices as they face a new teaching scenario where language(s) can be used to construct lecturers' identities. Therefore, lecturers can take up different identities because their language-choice acts depend on their communicative and identification purposes. Employing Membership-Categorisation Analysis (MCA) to examine classroom interaction, this paper examines the classroom practices of one EMI lecturer to explore how the orientation towards one language over the others implies a specific function associated with a particular identity. The alternation between languages reveals to what extent EMI lecturers accept or challenge the English-only policy and how lecturers position themselves as English-only or as translanguaging lecturers. This study documents lecturer's teaching behaviour, particularly how L1-choice acts can be more effective for certain purposes. Studying how lecturers draw from both their EMI-lecturer identity and their L1-lecturer identity, this paper shows how multilingual practices unfold in EMI and highlights the pedagogical value of the L1, hence advocating that the use of languages other than English has, after all, a particular purpose.